Novel role for gabapentin in neuroprotection of central nervous system in streptozotocine-induced diabetic rats - Baydas, G; Sonkaya, E; Tuzcu, M; Yasar, A; Donder, E (Nature Publ Group, 2005)
Aim: To investigate the effect of gabapentin on neural [neuron-specific enolase (NSE)] and glial markers [glial fibrillary acidic protein (GFAP) and S 10013] in different brain regions of diabetic rats. Methods: Diabetes was induced by a single C intraperitoneal injection of streptozotocine (50 mg/kg body weight). Rats in one diabetic group received gabapentin (50 mg(.)kg(-1.)d(-1)) and rats in the other diabetic group received vehicle only for 6 weeks. The levels of GFAP, S 10013, and NSE were determined by immunoblotting in the hippocampus, cortex, and cerebellum. Lipid peroxidation (LPO as malondialdehyde+ 4-hydroxyalkenals) and glutathione (GSH) levels were also determined in the same brain parts. Results: Total and degraded GFAP content and S100B protein expression in different areas of brain tissues significantly increased in diabetic rats compared to control rats. Similarly, NSE levels were also significantly elevated in hyperglycemic rats. In addition, there was a significant increase in LPO levels in the diabetic rat brain compared to control rat brains. Pretreatment with gabapentin prevented the upregulation of GFAP, S 10013, and NSE in all brain regions of diabetic rats. The level of LPO was reduced, but not completely halted, by treatment with gabapentin. Conclusion: These results suggest that diabetes causes glial and neuronal injury, possibly as a result of elevated oxidative stress, and that gabapentin protects neurons and glial cells. Thus, we predict that gabapentin treatment will attenuate the hippocampal and cortical neurodegeneration observed during diabetes mellitus in rats.
Keywords: gabapentin; glial fibrillary acidic protein; neurotrophic protein S100beta; phosphopyruvate hydratase; lipid peroxidation